Comparison of central corneal thickness: ultrasound pachymetry versus slit-lamp optical coherence tomography, specular microscopy, and Orbscan - Khaja, Wassia A (Clin Ophthalmol, 2015)
BACKGROUND: Central corneal thickness (CCT) can be measured by using contact and non-contact methods. Ultrasound pachymetry (US pachymetry) is a contact method for measuring CCT and is perhaps the most commonly used method. However, non-contact methods like scanning slit topography (Orbscan II), slit-lamp optical coherence tomography (SL-OCT), and specular microscopy are also used. Not many studies have correlated the measurement of CCT with all four modalities. The purpose of this study was to compare and correlate the CCT measurements obtained by US pachymetry with SL-OCT, specular microscopy, and Orbscan. METHOD: This is a prospective, comparative study done in an institutional setting. Thirty-two eyes of 32 subjects with no known ocular disease and best-corrected visual acuity of 20/20 were enrolled. CCT measurements were obtained using SL-OCT, specular microscopy, scanning slit topography (Orbscan), and US pachymetry. Three measurements were made with each instrument by the same operator. Mean, standard deviation, and coefficient of variation were calculated for CCT measurements acquired by the four measurement devices. Bland–Altman plot was constructed to determine the agreements between the CCT measurements obtained by different equipment. RESULTS: The mean CCT was 548.16±48.68 μm by US pachymetry. In comparison, CCT averaged 546.36±44.17 μm by SL-OCT, 557.61±49.92 μm by specular microscopy, and 551.03±48.96 μm by Orbscan for all subjects. Measurements by the various modalities were strongly correlated. Correlations (r(2)) of CCT, as measured by US pachymetry compared with other modalities, were: SL-OCT (r(2)=0.98, P<0.0001), specular microscopy (r(2)=0.98, P<0.0001), and Orbscan (r(2)=0.96, P<0.0001). All modalities had a linear correlation with US pachymetry measurements. CONCLUSION: In subjects with healthy corneas, SL-OCT, specular microscopy, and Orbscan (with correction factor) can be used interchangeably with US pachymetry in certain clinical settings. The four modalities showed significant linear correlations with one another.